Biometric Recognition 7th Chinese Conference, CCBR 2012, Guangzhou, China, December 4-5, 2012, Proceedings - Zheng, Wei-Shi; Sun, Zhenan; Wang, Yunhong; Chen, Xilin; Yuen, Pong C.; Lai, Jianhuang (Image Processing, Computer Vision, Pattern Recognition, and Graphics ;, 2012)
This book constitutes the refereed proceedings of the 7th Chinese Conference on Biometric Recognition, CCBR 2012, held in Guangzhou, China, in December 2012. The 46 revised full papers were carefully reviewed and selected from 80 submissions. The papers address the problems in face, iris, hand biometrics, speaker, handwriting, gait, soft biometrics, security and other related topics, and contribute new ideas to research and development of reliable and practical solutions for biometric authentication.